Penilaian Risiko Ergonomi Keselamatan Dan Kesehatan Kerja (K3) Pada Pekerja Kemplang Tunu Di Desa Meranjat Ii Kabupaten Ogan Ilir - Meilandi, Al Habib; Andarini, Desheila; Novrikasari, Novrikasari; Lestari, Mona (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
The majority of the population in Meranjat II Village, Ogan Ilir Regency, has a home industry of Kemplang Tunu. Kemplang tunu is snack from the South Sumatera region. Kemplang tunu is made from fish, tapioca flour, and other seasonings. Based on the results of initial observations, it is known that there are still kemplang workers who have awkward work postures, therefore to avoid the occurrence of work-related diseases or work accidents it is necessary to carry out an ergonomic risk assessment for kemplang tunu workers. The purpose of this study is to analyze the level of ergonomics risk in kemplang tunu workers in Meranjat II Village, Ogan Ilir Regency. The research design in this study is descriptive observational with case study design and the total object of this research is 8 kemplang tunu workers. The object selection technique in this study used a purposive sampling technique. The risk analysis method used is the Rapid Entire Body Assessment. The results of calculating the level of ergonomics risk using the REBA method on 4 respondents working in the dough-making section, 3 of 4 respondents get a score of 8-10 so that they are at High Risk and 1 respondent gets a score of 4-7 so that they are at the Medium Risk. And of the 4 respondents working in the kemplang roasting section, 3 of 4 respondents get a score of 8-10 so they are at the High Risk and 1 respondent gets a score of 4-7 so they are at Medium Risk .